2017
DOI: 10.2147/dddt.s131797
|View full text |Cite
|
Sign up to set email alerts
|

Drug–drug interaction of microdose and regular-dose omeprazole with a CYP2C19 inhibitor and inducer

Abstract: PurposeA microdose drug–drug interaction (DDI) study may be a valuable tool for anticipating drug interaction at therapeutic doses. This study aimed to compare the magnitude of DDIs at microdoses and regular doses to explore the applicability of a microdose DDI study.Patients and methodsSix healthy male volunteer subjects were enrolled into each DDI study of omeprazole (victim) and known perpetrators: fluconazole (inhibitor) and rifampin (inducer). For both studies, the microdose (100 μg, cold compound) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 16 publications
3
21
0
Order By: Relevance
“…In our study, in which we administered the same doses intravenously, metabolic ratios were similar, and the dose-normalized exposure with the 20-mg dose was only 7% larger than exposure with the microdose, and this difference was not statistically significant. When comparing our results with the findings of single oral omeprazole doses, 11 these findings indicated that the intravenous route of administration is much less susceptible to PK nonlinearity and suggest that microdose omeprazole is well suited as a probe drug especially considering the new drug-drug interaction guideline of the FDA.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…In our study, in which we administered the same doses intravenously, metabolic ratios were similar, and the dose-normalized exposure with the 20-mg dose was only 7% larger than exposure with the microdose, and this difference was not statistically significant. When comparing our results with the findings of single oral omeprazole doses, 11 these findings indicated that the intravenous route of administration is much less susceptible to PK nonlinearity and suggest that microdose omeprazole is well suited as a probe drug especially considering the new drug-drug interaction guideline of the FDA.…”
Section: Discussionsupporting
confidence: 57%
“…For omeprazole, limited microdose data in healthy volunteers indicate a more than proportional concentration increase of oral omeprazole between doses of 0.1 and 20 mg. As a consequence, plasma drug exposure (AUC 0-∞ ) after microdoses was only 0.35-0.39 of the dose-normalized AUC of the regular dose. 11 Thus, the difference of omeprazole plasma concentration between microdose and regular dose was almost 3-fold. In our study, in which we administered the same doses intravenously, metabolic ratios were similar, and the dose-normalized exposure with the 20-mg dose was only 7% larger than exposure with the microdose, and this difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…A majority of PPIs are metabolized mainly by CYP2C19 and partially by CYP3A4 (Klotz et al, 2004;Klotz, 2006;de Bortoli et al, 2013). The pharmacokinetics of PPIs such as omeprazole can be significantly affected by CYP2C19 polymorphism (Qiao et al, 2006;Hunfeld et al, 2008) and coadministered CYP2C19 inhibitors (Park et al, 2017). Ilaprazole overcomes the CYP2C19-related limitations of other PPIs.…”
Section: Introductionmentioning
confidence: 99%